Bridging between Beliefs and Needs of Language Teachers in Philippines: Personal Qualities, Strategies, and Framework during COVID-19 Pandemic - Ramos, Ariel; Baldespiñosa, Maritoni (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
This qualitative case study examines the constraining effects of the internet connectivity to English language teaching communities migrated to online instruction during/ after the COVID-19 pandemic based on the teacher’s beliefs in the Philippines’ context. The paper also explores the innovative English teaching strategies, needed personal qualities, and framework for the teacher's innovative teaching to navigate their way in delivering instruction under alternative modalities. Through the focus group discussion employing a validated open-ended interview guide as an instrument for data gathering, information was processed through codes and coding techniques outlined by Miles and Huberman (1994) along with the aid of a licensed NVivo 12 software in order to examine the teachers’ beliefs on creativity, as well as their personal qualities and how these variables are transformed into innovative offline English teaching strategies. Findings reveal that the five emerging underlying themes on the teachers’ beliefs about creativity translated into innovative English teaching strategies for offline instruction are learnability, non-exclusivity, essentiality, physical context dependency, and non-physical context dependency. Moreover, there are also five developing significant COVID-19 personal qualities for English teachers that were found, including being creative, optimistic, versatile, inventive, and devoted. These findings became cornerstones of the innovative offline English language teaching framework that can be used as a practical guide in academic communities worldwide where internet connectivity is not dependable for online instruction.